2022
DOI: 10.1039/d2sm00703g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a multifunctional organogel and its electrochemical properties

Abstract: A facile methodology to fabricate high elastic organogel for supercapacitors is demonstrated. Stable polymer organogel was obtained in DMSO by simply esterification reaction. This organogel showed high mechanical performance, flexibility,high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…PVA/4SD organogel electrolytes also demonstrate weak redox peaks because the formation of ester bonds between PVA and 4SD and acid catalysis cause ester bond hydrolysis, which belongs to a redox process. 54 By comparison (Figure 4D), it can be found that the organogel electrolyte with KI has very high ionic conductivity, up to 30.12 mS cm −1 , on account of KI can increase the ion concentration and act as a plasticizer to promote the movement of ions in the electrolyte. 55 Nyquist plots for PVA, PVA/4SD, and PVA/ power supplies and successfully lit a small 3 V calculator (Figure 4L).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…PVA/4SD organogel electrolytes also demonstrate weak redox peaks because the formation of ester bonds between PVA and 4SD and acid catalysis cause ester bond hydrolysis, which belongs to a redox process. 54 By comparison (Figure 4D), it can be found that the organogel electrolyte with KI has very high ionic conductivity, up to 30.12 mS cm −1 , on account of KI can increase the ion concentration and act as a plasticizer to promote the movement of ions in the electrolyte. 55 Nyquist plots for PVA, PVA/4SD, and PVA/ power supplies and successfully lit a small 3 V calculator (Figure 4L).…”
Section: Resultsmentioning
confidence: 96%
“…The CV curves of PVA, PVA/4SD, and PVA/4SD/KI organogel-based SCs are compared at a scanning rate of 25 mV s –1 (Figure C). PVA/4SD organogel electrolytes also demonstrate weak redox peaks because the formation of ester bonds between PVA and 4SD and acid catalysis cause ester bond hydrolysis, which belongs to a redox process . By comparison (Figure D), it can be found that the organogel electrolyte with KI has very high ionic conductivity, up to 30.12 mS cm –1 , on account of KI can increase the ion concentration and act as a plasticizer to promote the movement of ions in the electrolyte .…”
Section: Resultsmentioning
confidence: 97%
“…With the continuous progress and development of wearable electronic technology, flexible electronic products with the characteristics of portability, wearability, collapsibility, miniature, and lightweight have been paid more and more attention. As we know, in lots of energy storing devices, flexible solid-state supercapacitors have become one of the most hopeful flexible energy storage devices due to their large specific capacitance, rapid charging and discharging properties, wonderful stability, and excellent mechanical properties. The rational design of electrode or electrolyte materials and the optimization of device configuration have become the direction of development to build high-performance flexible supercapacitors (FSCs). Conductive gels with intrinsic flexibility, significant mechanical recycling, and remarkable ionic conductivity can not only be used as ideal materials for FSC electrolytes but also have considerable applications in tissue engineering, drug delivery, water treatment, bioengineering, and many other fields.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels, comprising three-dimensional polymeric networks and aqueous mediums, have been regarded as promising electrolytes owing to their dimensional stability and chemical activity. [1][2][3] A few proton-conductive hydrogels have been developed by adding inorganic acids or incorporating acid moieties into polymeric networks. [4][5][6] Regulating acid concentration is regarded as an effective way to tune the conductivity of hydrogels.…”
Section: Introductionmentioning
confidence: 99%